The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.29271/jcpsp.2020.08.822
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hypertension with Non-HDL Cholesterol in Patients with Type 2 Diabetes Mellitus

Abstract: Objective: To determine the association of hypertension with Non-HDL Cholesterol (Non-HDL.C) among patients with type 2 diabetes mellitus. Study Design: Descriptive study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Above all, the mean Non-HDL-c level was higher in hypertensives than in normotensive respondents. These ndings are generally in support of several studies that have reported a positive association between Non-HDL-c and hypertension, arterial stiffness and ischemic heart disease, and a cardiovascular event (de Oliveira Alvim et al, 2017;Zaka et al, 2020;Calling et al, 2021). Our…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Above all, the mean Non-HDL-c level was higher in hypertensives than in normotensive respondents. These ndings are generally in support of several studies that have reported a positive association between Non-HDL-c and hypertension, arterial stiffness and ischemic heart disease, and a cardiovascular event (de Oliveira Alvim et al, 2017;Zaka et al, 2020;Calling et al, 2021). Our…”
supporting
confidence: 91%
“…While several studies from different populations have reported that RC and Non-HDL-c (Zaka et al, 2020;Sun et al, 2022;Zheng et al, 2022) have more predictive power than LDL cholesterol in detecting CVD, very few studies have been done in sub-Saharan Africa on people with diabetes. The understanding of the role of obesity as a risk factor is still debated.…”
Section: Introductionmentioning
confidence: 99%
“… 73 In contrast, Zaka and colleagues reported no significant difference in the mean of non‐HDL‐C among diabetic patients with hypertension and without hypertension (156.35 ± 38.52 mg/dL vs. 156.81 ± 45.82 mg/dL; p > .05). 74 The reason for these different findings may be due to the different enrolled populations in studies. We observed that women had higher levels of non‐HDL‐C compared to men.…”
Section: Discussionmentioning
confidence: 99%